Children with primary complex motor stereotypies show impaired reactive but not proactive inhibition. (March 2020) - Mirabella, Giovanni; Mancini, Christian; Valente, Francesca; Cardona, Francesco
Abstract: Typically, the inability to control urges tends to be ascribed to a lack of inhibitory control. Primary complex motor stereotypes (p-CMS), occurring in children with an otherwise typical development, represent a remarkable example of involuntary, complex, repetitive and apparently purposeless movements. However, it has never been tested whether the core of the pathophysiology of p-CMS lies in a deficit of inhibitory control. To fill this gap, we assessed whether children with p-CMS exhibit an impairment of one or both types of inhibition, i.e., reactive inhibition (the ability of subjects to react to a stop-signal) and/or proactive inhibition (the ability of subjects to shape their response strategies according to the context in which subjects are embedded). We compared inhibitory control of 20 drug-naïve patients with p-CMS (mean age ±SD: 7.4 ± 1.1) with that of 20 age- and gender-matched typically developing children (7.5 ± 1.2) via a reaching version of the stop-signal task. We found that while reactive inhibition is significantly impaired, proactive control in children with p-CMS is similar to that of the control group. The deficit in reactive control might explain why patients are unable to inhibit involuntary movements when triggered by states of mind such as stress, fatigue, boredom or excitement. Nevertheless, the absence of a deficit in proactive control suggests that patients are aware of the environmental context and thus they quickly stop the stereotypic movements when their attention is diverted. All in all, our findings might explain two key features of the p-CMS phenotype.